Metabolic syndrome and its risk factors among adults residing in urban community in Kerala - Asha KP; Indu D; Beevi F (Journal of Medical and Scientific Research)
Background: Metabolic syndrome is a complex condition characterized by abdominal obesity, insulin resistance, hypertension, and hyperlipidaemia. This cluster of health issues increases the risk of severe diseases, including cardiovascular disease, diabetes, and stroke. Recognizing its serious impact, the Adult Treatment Panel III (ATP III) of the National Cholesterol Education Programme has identified metabolic syndrome as a significant public health concern in the modern era. The study aims to evaluate the combination of these interrelated health risks makes MS a serious health problem throwing challenges to clinicians and public health specialists.